Strategi Guru dalam Menerapkan Model Pembelajaran Problem Based Learning di Raudhatul Athfal Al-Fath - Shofiyati Shofiyati; Sumiyati Sumiyati; Naila Ismiyatussulha (Tinta Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
Methods are Problem-based learning used as a driving force for students to learn to integrate and organize the information obtained so that later it can always be remembered and applied to solve the problems that will be faced.This study aims to determine the teacher's strategy in implementing the problem based learning at RA Al-Fath Sentul based on: Context, Input, Process and product. To find out the supporting and inhibiting factors in the implementation of the Problem Based Learning Strategy at Ra Al-Fath Sentul. The type of research used in this research is qualitative. Data collection techniques used several methods, data collection in order to obtain the necessary data including, observation, interviews (interviews) and documentation. The results showed the teacher's strategy in applying the problem based learning at RA Al-Fath Sentul based on the evaluation of context, input, process, and product, namely: (a) Activities orienting students to problems Teachers orienting students to problems by presenting problems and then motivating students to be active in solving the problem, (b) The teacher defines and organizes students to learn by helping students in organizing learning tasks in solving the given problem, (c) The teacher develops and presents the work of drawing or coloring by asking a group that has done.